Caffeine effects on physical performance and sport-specific skills in elite youth soccer players: A randomised trial using the balanced placebo design - Bezuglov, E.; Vakhidov, T.; Morgans, R.; Malyakin, G.; Emanov, A.; Koroleva, E.; Kapralova, E.; Talibov, O. (Sports, 2025)
The aim of the study was to examine the safety and effects of relatively high caffeine doses on physical performance and sport-specific skills of young elite soccer players. Fifty-four soccer players from an elite Russian soccer academy participated in the blinded randomised placebo-controlled study with a double-blinded and balanced design. Participants were divided into four groups: group 1 CAF/CAF; group 2 CAF/PLA group 3 PLA/PLA and group 4 PLA/CAF. All participants were administered 400 mg of caffeine or the placebo. The data demonstrated that a single 400 mg caffeine administration 60 min before exercise had a positive effect on repeated sprint ability (RSA) test parameters such as fatigue index (for both groups p < 0.001) and percentage decrement score (for both groups p < 0.001). In group 4, statistically significant improvements were also found when performing the fourth and sixth sprint during the RSA test (p = 0.039 and p = 0.005, respectively). Group 1 also showed a statistically significant improvement in dribbling speed performance (p = 0.048). It was demonstrated that the number of adverse events in all four groups was not different (p = 0.56). A single administration of 400 mg of caffeine 60 min prior to maximal intensity physical activity can be considered reasonable and safe for young elite soccer players.